Combination of Drug Delivery Properties of PAMAM Dendrimers and Cytotoxicity of Platinum(IV) Complexes-A More Selective Anticancer Treatment? - Yvonne Lerchbammer-Kreith; Michaela Hejl; Petra Vician; Michael A. Jakupec; Walter Berger; Mathea S. Galanski; Bernhard K. Keppler (MDPI AG, 2023)
Based on their drug delivery properties and activity against tumors, we combined PAMAM dendrimers with various platinum(IV) complexes in order to provide an improved approach of anticancer treatment. Platinum(IV) complexes were linked to terminal NH2 moieties of PAMAM dendrimers of generation 2 (G2) and 4 (G4) via amide bonds. Conjugates were characterized by 1H and 195Pt NMR spectroscopy, ICP-MS and in representative cases by pseudo-2D diffusion-ordered NMR spectroscopy. Additionally, the reduction behavior of conjugates in comparison to corresponding platinum(IV) complexes was investigated, showing a faster reduction of conjugates. Cytotoxicity was evaluated via the MTT assay in human cell lines (A549, CH1/PA-1, SW480), revealing IC50 values in the low micromolar to high picomolar range. The synergistic combination of PAMAM dendrimers and platinum(IV) complexes resulted in up to 200 times increased cytotoxic activity of conjugates in consideration of the loaded platinum(IV) units compared to their platinum(IV) counterparts. The lowest IC50 value of 780 ± 260 pM in the CH1/PA-1 cancer cell line was detected for an oxaliplatin-based G4 PAMAM dendrimer conjugate. Finally, in vivo experiments of a cisplatin-based G4 PAMAM dendrimer conjugate were performed based on the best toxicological profile. A maximum tumor growth inhibition effect of 65.6% compared to 47.6% for cisplatin was observed as well as a trend of prolonged animal survival.